Groundwater transport of Cu in laterites in Zambia. (May 2015) - Lweya, Charity; Jessen, Søren; Banda, Kawawa; Nyambe, Imasiku; Koch, Christian Bender; Larsen, Flemming
Graphical abstract: Highlights: Mineralogical investigations have been conducted on a lateritic in NW Zambia. Sorption experiments with pH = 2.8 show insignificant Cu sorption to the laterite. Sorption experiments at pH 4.5 show a maximum sorption to laterite of 239 mg/kg. Cu sorption in the laterite occur must likely to kaolinite and iron oxides minerals. In groundwater with pH 4.5, Cu will move 15 cm per year through the laterite. Abstract: The risk of transporting copper (Cu) in near surface laterite with acid groundwater was studied down gradient of a newly constructed open mine in the North Western Province of Zambia. The assessment was based on results obtained from field and laboratory work and geochemical modeling. Large seasonal variations in the groundwater elevation is changing the subsurface water flow from a dominating Darcy flow in the laterite during the rainy season to a dominating fracture flow in the deeper, fractured gneiss in the dry season. As the major groundwater flow occurs in the laterite, and the low pH of the groundwater is also observed in the laterite, mineralogical and sorption experiments were confined to this unit where the risk of a Cu groundwater transport is highest. The mineralogy of the laterite was studied using X-ray analysis, infrared and Mössbauer spectroscopy, and results revealed a homogeneous composition of strongly weathered primary silica minerals, mainly quartz, muscovite, biotite and feldspars, and secondary minerals dominated by disordered kaolinite, iron oxide (goethite/hematite mixtures or solely goethite) and minute amounts of vermiculite. Cu sorption to the laterite was determined from batch experiments using initial Cu concentrations between 10 and 400 mg/L and pH of 2.8 and 4.5. At pH 4.5 a maximum sorption capacity of 239 mg/kg was found for aqueous equilibrium Cu concentrations of 150 mg/L. For aqueous Cu concentrations below 150 mg/L, a nearly linear sorption was observed with Kd value of 18. Cu sorption to the laterite is negligible for pH 2.8. The mineralogical study of the laterite suggests that Cu predominately sorbs to the minerals iron oxides and kaolinite.